PELATIHAN KETRAMPILAN KREASI NUGGET LELE BERGIZI KEPADA IBU BALITA DAN PENYULUHAN GIZI UNTUK PENCEGAH KEJADIAN STUNTING DI WILAYAH GUNUNGPATI - Widayani, Sus; Triatma, Bambang; Pratama, Muh. Nur Agung (P-2776-3072)
Abstract: The danger of stunting threatens Indonesian children. The danger of stunting threatens Indonesian children. Stunting is when toddlers are shorter than their age, caused due to chronic malnutrition at 1000PHK from fetus to 2 years of age. The physical and brain development of stunted children is hampered and susceptible to disease, resulting in difficulty achieving. When adults are easily overweight so they are at risk of developing degenerative diseases. At the productive age, stunting children earn 20% less than children with optimal growth. Stunted children reduce the country's gross domestic product by 3%. For Indonesia, the loss due to child editing reaches Rp. 300 trillion per year. It is very necessary to prevent stunting, one of which is by doing the dedication to help mothers of toddlers provide nutritious food supplies to their toddlers so that they are healthy and have a good nutritional status so as to prevent stunting in their area. Fish is processed food that attracts and likes children (Widayani and Triatma, 2018). Reinforcement with a lack of attention to children's consumption, and often children eat only for pleasure. This is also supported by the low level of fish consumption in the city of Semarang (11.3 kg / year / capita which should have been 31.4 kg / year / capita). If this condition is allowed to drag on, toddlers will grow up to become children who do not like to eat fish so that the fulfillment of animal protein needs in the body is lacking. The aim is to provide nutrition education and training on healthy and nutritious catfish nuggets processing to prevent stunting. Methods of counseling and training for mothers of toddlers so that they are skilled at creating catfish nuggets. The nugget-making practice adds to the enthusiasm of toddler mothers. There was a change in the mindset of the mothers after the nutrition counseling activities and training in processing nutritious healthy nuggets. The mothers hope to be given back counseling and practice of fish processing and nutritious food on a regular basis. The hope in the future is that children will love to eat fish so that a nutritionally aware society will be realized.